A Meta-analysis of the Types and Outcomes of Conservative Excisional Surgery for Recalcitrant or Infected Diabetic Toe Ulcers. Issue 2 (April 2020) - Yammine, Kaissar; Assi, Chahine
Although they occur frequently, diabetic toe ulcers (DTUs) are poorly investigated. Long-term antibiotics or toe amputation are the usual indications for complicated DTU treatment. Some authors reported good to excellent results following conservative surgery (CS) for recalcitrant or infected wounds; yet no systematic review has been published. Seven studies, comprising 290 patients with 317 ulcers, met the inclusion criteria of this meta-analysis. Three types of CS were found: resection arthroplasty of the interphalangeal joint, toe-sparing bone excision (internal pedal amputation), and distal Symes amputation. The meta-analytical results were as follows: healing rate of 98.3%, healing time of 6.8 ± 3.9 weeks, recurrence rate of 2.3%, wound dehiscence/recurrent infection rate of 6.4%, skin necrosis rate of 2.8%, and revision surgery rate of 7.4%. Subgroup analyses showed no significant differences in outcomes between recalcitrant ulcers and infected ulcers nor between surgery types. Significance was found in relation to ulcer location; when compared with the hallux, DTU on the lesser toes demonstrated better outcomes. Compared with the reported overall results of standard of care associated with antibiotics or toe amputation of complicated DTUs in the literature, CS seems to be a better option for the treatment of recalcitrant or infected DTUs. Levels of Evidence: Level III